(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the process of successful public offering (IPO, SPO) of stocks by joint-stock companies operating in our country. Additionally, the opinions of both foreign and domestic scholars who have conducted research on this topic, as well as the experiences of foreign countries, are considered to derive conclusions, modern approaches, and recommendations for improving the practice of public offering of stocks in our country.